ANALISIS KELAYAKAN USAHA PEMBIBITAN PADI DI KECAMATAN LABUHAN HAJI KABUPATEN LOMBOK TIMUR - FADLI, FADLI; Yusuf, M; FR, Aeko Fria Utama (AGROTEKSOS; Vol 33 No 1 (2023): Jurnal Agroteksos April 2023DO - 10.29303/agroteksos.v33i1.829, 2023)
The aims of this study are to analyze the costs, income and feasibility of a rice nursery in Labuhan Haji District, East Lombok Regency. The method used in this study is descriptive method, while data collection was carried out using a survey technique. Data were analyzed descriptively. The results showed that: The average production costs incurred by farmers in the rice nursery business amounted to IDR 5,105,000/ha, with an income of IDR 18,628,000/ha. The value of R/C and B/C ratio of rice nursery business is 5.43 and 0.78